The Application of the CRISPR/Cas9 System in the Treatment of Hepatitis B Liver Cancer - Wei Lv MSc; Tao Li PhD; Shanshan Wang MSc; Huihui Wang MSc; Xuemei Li MSc; Shubing Zhang MSc; Lianzi Wang MSc; Yuanhong Xu PhD; Wei Wei PhD (Technology in Cancer Research & Treatment, 2021)
The clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein 9 (Cas9) system was originally discovered in prokaryotes and functions as part of the adaptive immune system. The experimental research of many scholars, as well as scientific and technological advancements, has allowed prokaryote-derived CRISPR/Cas genome-editing systems to transform our ability to manipulate, detect, image, and annotate specific DNA and RNA sequences in the living cells of diverse species. Through modern genetic engineering editing technology and high-throughput gene sequencing, we can edit and splice covalently closed circular DNA to silence it, and correct the mutation and deletion of liver cancer genes to achieve precise in situ repair of defective genes and prohibit viral infection or replication. Such manipulations do not destroy the structure of the entire genome and facilitate the cure of diseases. In this review, we discussed the possibility that CRISPR/Cas could be used as a treatment for patients with liver cancer caused by hepatitis B virus infection, and reviewed the challenges incurred by this effective gene-editing technology.